Reliability of the report of electoral campaigns to the portuguese Assembly of the Republic (2005 to 2011) - Carvalho, Ellene (2020)
Act no. 19/2003 sets out the legal framework applicable to the portuguese electoral campaigns’ accounts, which are audited by the Constitutional Court. The present investigation aims to study if this framework ensures the faithful representation of the reported information. We analysed the electoral campaigns’ accounts to the Assembly of the Republic of years 2005, 2009 and 2011. The main conclusion is the lack of reliability of these accounts, with the existence of recurrent infractions common to various parties, being worth to mention the low fines applied in relation to the infraction amounts. It should be noted that the accounts are submitted without being rectified and that the revenues/expenses with infractions are kept in the accounts (also contributing to the amount of the government grant received). Thus, one can conclude that the benefits that political parties may obtain from such infractions will be greater than the cost of any fines, which may limit the scope of the legal framework in question